CORRELATIONS OF MORPHO-AGRONOMIC CHARACTERISTICS AND QUALITY COMPONENTS OF BIRDSFOOT TREFOIL (LOTUS CORNICULATUS L.) - Radić, Prof. Dr. Vojo; Komljenovic, ilija; Petkovic, Borislav (Journal of Agricultural Sciences (Belgrade), 2024)
: Birdsfoot trefoil is a perennial legume for the production of high-quality forage. Improving the production and quality of fodder is one of the strategic goals in breeding programs. Genotypes for this experiment were selected from promising offspring collected from local populations in Bosnia and Herzegovina. An experiment with eight genotypes (7 prospective lines and 1 variety) was set up in a randomized block system with four replications. In the first growth, 11 components of the yield and quality of green mass were analyzed, and in the second four more parameters for seed production. Pearson's correlation coefficients were determined. In the first growth, highly significant correlations were found between plant height and the proportion of leaves (0.85**) as well as the yield of green mass and dry matter (0.81**), while a high negative correlation was found between non-nitric extract matter (NNEM) and content of crude proteins (-0.79**). In the second increase, statistically highly significant (p˂0.01) positive correlations between (NNEM) content and ash (0.77**) were observed. Statistically significant (p˂0.05) positive relationships were found between: green mass yield and dry matter yield (0.81**), green mass yield and stem thickness (0.79*), seed yield and number of pods (0.83*) and cellulose content and plant height (0.73*). The identification of positive correlative relationships for certain productive and nutritional traits will be used in breeding programs for the creation of new varieties with improved fodder quality.
Keywords: Lotus corniculatus L., morphological traits, agronomic traits, correlative relationships.